Gastroesophageal reflux disease - unit description, diagnosis and treatment - Raban, Michał; Żak, Artur; Litak, Jakub; Turska, Monika; Grochowski, Cezary (Journal of Education, Health and Sport, 2017)
Many GPs are increasingly dealing with patients complaining of ailments likely to suggest gastro-esophageal reflux disease (GERD). These symptoms include heartburn, abdominal pain, and a feeling of esophageal reflux (regurgitation). GERD is one of the most common gastrointestinal diseases that gastroenterologists meet in their practice (1, 2). In North America the problem is affected from 18.1% to even 27.8% of the population. The situation is similar in Europe, where the proportion of people with reflux symptoms is in the range of 8.8% - 25.9%. Among European countries, the prevalence of GERD symptoms is higher in the north of the continent than in the south. The growing problem of overweight and obesity that makes GERD more and more recognized in the population of children and adolescents (3) is a worrying fact. Interestingly, reflux-related complaints are much less frequent in eastern Asia, affecting only 2.5% -7.8% of the population (4).